2024
DOI: 10.1021/acsnano.3c12925
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Electrostatically Generated Magnetoresistance in Chiral Systems without Spin-Dependent Transport

Sytze H. Tirion,
Bart J. van Wees

Abstract: Significant attention has been drawn to electronic transport in chiral materials coupled to ferromagnets in the chirality-induced spin selectivity (CISS) effect. A large magnetoresistance (MR) is usually observed, which is widely interpreted to originate from spin (dependent) transport. However, there are severe discrepancies between the experimental results and the theoretical interpretations, most notably the apparent failure of the Onsager reciprocity relations in the linear response regime. We provide an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
(227 reference statements)
0
0
0
Order By: Relevance
“…Interestingly, recent low-temperature spin-polarized scanning tunneling microscopy and spectroscopy measurements on single chiral heptahelicene molecules sublimed in vacuo from a racemic mixture onto the single-crystalline cobalt bilayer of nano-islands on a Cu(111) surface found that thermal enhancement mechanisms are not the essential ingredients for CISS . Moreover, an alternative mechanism was suggested for the origin of the two-terminal magnetoresistance linear response in chiral systems coupled to a ferromagnet …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent low-temperature spin-polarized scanning tunneling microscopy and spectroscopy measurements on single chiral heptahelicene molecules sublimed in vacuo from a racemic mixture onto the single-crystalline cobalt bilayer of nano-islands on a Cu(111) surface found that thermal enhancement mechanisms are not the essential ingredients for CISS . Moreover, an alternative mechanism was suggested for the origin of the two-terminal magnetoresistance linear response in chiral systems coupled to a ferromagnet …”
Section: Introductionmentioning
confidence: 99%